Design brushless DC motor control by using proportional-integral strategy for a smart storage cabinet system - Quang Dich Nguyen; Viet Thang Tran; Quang Dang Pham; Van Nam Giap; Minh Hiep Trinh (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
As well know, the use of high technology is more and more encouraged in many countries to decrease the costs, time, and human resources. This paper presents a speed control of brushless DC motor (BLDC), which was applied for the smart storage cabinets. BLDC motor is proposed due to its low costs, high torque, and high performance. The proportional-integral (PI) controller is constructed for the speed control of the movement of cabinet systems. First, the mathematical model and transfer function of the BLDC motor is rewritten to show the structure of the BLDC motor. Second, the proposed PI controller is designed based on the tuning Ziegler-Nichols method and the PI controller is also expressed by the discretized form for BLDC motor. Third, the working principle of BLDC motor is clearly represented and analyzed. Forth, the detail configuration of the experimental system is presented. The STM32 microcontroller unit (MCU) was used to execute. Finally, the experimental test was implemented to validate the power of the proposed controller in practical cases. The experimental results at no-load and load were shown that the power of proportional integral derivative (PID) controller is good at tracking the desired speed signals.